Multiple tail vein injections of adipose-derived mesenchymal stem cells ameliorate allergic rhinitis in mice: superior efficacy of prolonged regimens - Xie, Yutong; Zhang, Jiacheng; Yang, Wenhan; Pan, Zhiyu; Wang, Lian; Lai, Ju; Fan, Kai; Dai, Yalei; Zuo, Keqiang; He, Fei; Gao, Zhengliang; Yu, Shaoqing (Frontiers in Immunology, 2025)
BackgroundAdipose derived mesenchymal stem cells (ADSCs) are a subset of mesenchymal stem cells (MSCs), showing broad anti allergic effects in type 2 inflammation. Their systemic efficacy in allergic rhinitis (AR) is not well defined. In this study, we tested whether prolonged and repeated ADSC delivery improves outcomes in the AR mouse model.MethodsAn ovalbumin (OVA) induced AR mouse model was established. Mice were divided into three groups: a control group, an AR model group, and an ADSC treatment group. Each group was administered phosphate buffered saline (PBS) or ADSCs via tail vein infusion during defined treatment phases. Symptom severity including nasal scratching and sneezing was recorded before and after treatment. Nasal mucosal pathology and inflammatory biomarkers were assessed at the same time points. Therapeutic efficacy was evaluated by the therapeutic efficacy index (TEI).ResultsSystemic tail vein injection of ADSCs significantly attenuated AR symptoms and nasal inflammation. Treated mice exhibited decreased frequencies of nasal scratching and sneezing. Consistently, serum specific immunoglobulin E (sIgE), immunoglobulin G1 (IgG1) and transforming growth factor beta (TGF-β) were also reduced. Concurrently, both transcriptional and cytokine profiling indicated an increased ratio of T helper 1 (Th1) to T helper 2 (Th2) related cytokines, indicating restoration of immune balance. Besides, long-term (4-weeks) ADSC therapy with multi-injection yielded superior efficacy over short-term (1-week and 2-weeks) regimens in therapeutic efficacy index (TEI) analysis.ConclusionSystemic ADSC delivery through the tail vein alleviated AR in mice. Extended multi-injection schedules produced greater benefit. ADSCs represent a promising systemic immunomodulatory therapy for AR, with enhanced efficacy under longer treatment cycles.